Physiological Characterisation of Nitrogen Fixing Bacteria in Pure and Mixed Cultures - Meta,Xhilda (2025)
The scope of this Master Thesis project is divided in two parts. In the first part, the objective is to characterise various strains of Azotobacter vinelandii under diazotrophic conditions with regards to growth rate and production of metabolites, such as ammonium or PHB. This will allow for an assessment on which nitrogen fixing strain displays the most promising results for use in the second part of the thesis. The second part covers the evaluation of a synthetic co-culture of Azotobacter vinelandii with Pseudomonas putida in nitrogen-free medium. Positive controls of both strains and media conditions were performed to build more favourable comprehension of metabolic activities for these two strains. A series of methods, assays and techniques were used and modified for a better and well-built story that explains this abundance of results in the most comprehensive and standardized way. This thesis presented affirmative results on the use of A. vinelandii and P. putida as cooperating microorganisms in a co-culture, with data trends supporting the established hypotheses on synergistic effects of this consortium. This project also introduced Flow Cytometry methods for detection of cell populations, as well as demonstrated the potential of A. vinelandii, as a strain with a plethora of benefits in creating sustainable and highly efficient microbial applications.
Keywords: Azotobacter; Nitrogen fixation; PHB; Co-culture; Pseudomonas; Flow cytometry; Applied microbiology